Effects of fancy job titles and pictures in recruitment advertisements. - Lim, Samantha HuiYing. (2008)
This study postulates that the presence of a Fancy job title or a Picture in a recruitment advertisement has a greater impact on a job seeker’s Job Attitude and Intention to Apply for a job favourably. We used a questionnaire, simulating a recruitment print advertisement page for a Marketing position in the newspapers. The experiment was carried out in a controlled environment on 373 graduating Marketing majors. Participants read a scenario and answered questions regarding Job Attitude and Intention to Apply for four advertisements.